55 Long term clinical outcomes from use of sirolimus coated balloon in coronary intervention; data from a real-world population. (4th June 2021) - Loku Waduge, Bhagya Harindi; Kalkat, Harkaran; Fawzy, Ameenathul Mazaya; Saif, Abdullah; Athukorala, Sampath; Bhatia, Gurbir; Kumar, Nitin; Freestone, Bethan; Ment, Jerome; Lee, Kaeng; Pitt, Michael; Pulikal, George; et al.
Abstract : Background: The use of drug coated balloons (DCBs) in coronary intervention is escalating. There are two drugs of choice for coating either DCBs or drug eluting stents: Paclitaxel or Sirolimus. Most available DCBs are coated with Paclitaxcel, due to pre-existing, extensive data that support good clinical outcomes. With drug eluting stents both the literature and hence clinical practice favour Sirolimus over Paclitaxcel. This is due the cytostatic properties and wide therapeutic window of Sirolimus. However, there is very limited data on Sirolimus coated balloons (SCBs). We report a long-term follow-up with this relatively new technology from our centre. Methods: A retrospective analysis was conducted on all patients treated with an SCB between March 2018 and October 2020. Follow-up was achieved with clinic visits, telephone calls and admission records. The outcomes measured include cardiac death, target-vessel myocardial-infarction, target lesion revascularisation and MACE (combination of cardiac death, target-vessel MI and TLR). Results: 533 patients (690-lesions) with a mean age of 65.4 (range; 37-90) were treated with an SCB. 79% (n=419) were male, 314 (59%) were in the setting of acute coronary syndrome, 40% (n=211) had diabetes and 60% (n=414) had DCB in de-novo lesions. Small vessels accounted for 59% of cases (n=406). Pre-dilatation was performed in 97% (n=670) of cases. Bailout stenting (with a drug eluting stent) was required in 6.5% lesions (n=45), of which 11 were due to dissections and 34 were due to >50% recoil following DCB use. The mean diameter and length of DCBs were 2.8 mm and 26.3 mm respectively. During a median follow-up of 572 days (IQR: 381 - 868); cardiac death occurred in 15 patients (3%). Target vessel MI was in 4%; n=21, TLR per lesion and per patient were 10% (n=72 and n=55 respectively). The overall MACE rate was 12%. There were no documented cases of acute vessel closure. Conclusions: The results from long term follow-up with this relatively new technology DCB are encouraging with low rates of hard endpoints and acceptable rates of TLR and MACE despite complex group of patients (59% ACS and 40% diabetics) and lesion subsets (40% restenotic lesions and 59% small vessels). This suggests that SCBs can be used in both restenotic and de novo small vessel lesions with acceptable clinical outcomes. However, in order to further inform clinical practice, more longer-term data on SCBs compared with Paclitaxel coated balloons is needed. Conflict of Interest: None to declare